Body roundness index and its role in predicting COPD risk: insights from the English Longitudinal Study of Aging and the health and retirement study - Li, Longqian; Qin, ZhuoLin; Lin, Mingzhi; zhang, Chun; Wang, Cheng (Frontiers in Medicine, 2025)
BackgroundChronic obstructive pulmonary disease (COPD) is one of the most common chronic respiratory diseases worldwide. This study aims to investigate the relationship between the Body Roundness Index (BRI) and COPD in individuals aged 45 and older.MethodsThis study included 5818 participants from waves 2 to 9 (2004–2019) of the English Longitudinal Study of Aging (ELSA) and 6928 participants from waves 8 to 10 (2006–2021) of the Health and Retirement Study (HRS). Initially, univariate analysis, univariate Cox regression analysis, and trend analysis were conducted to preliminarily screen the variables. The variance inflation factor (VIF) was used to detect multicollinearity and ensure the independence of the selected variables. Subsequently, multivariate logistic regression and multivariate Cox regression models were employed to assess the relationship between the Body Roundness Index (BRI) and chronic obstructive pulmonary disease (COPD). Restricted cubic spline (RCS) analysis was applied to further explore the nonlinear relationship between BRI and COPD. Finally, sensitivity analysis was performed to validate the robustness of the model results.ResultsThe results from both datasets indicate a significant association between the Body Roundness Index (BRI) and chronic obstructive pulmonary disease (COPD) (ELSA: OR (95% CI) = 1.193 (1.074–1.321), P = 0.001; HRS: OR (95% CI) = 1.160 (1.094–1.228), P < 0.001). As BRI increases, the incidence of newly diagnosed COPD significantly rises (ELSA: HR (95% CI) = 1.149 (1.034–1.273), P = 0.009; HRS: HR (95% CI) = 1.114 (1.054–1.177), P < 0.001). The optimal cutoff analysis revealed a significant difference in COPD risk between the high and low BRI groups (ELSA: P = 0.0037; HRS: P = 0.0085). Restricted cubic spline (RCS) analysis further demonstrated a “J-shaped” relationship between BRI and COPD.ConclusionThis study demonstrates a significant association between the Body Roundness Index (BRI) and chronic obstructive pulmonary disease (COPD). The increase in BRI is significantly associated with both the incidence of COPD and newly diagnosed cases. Restricted cubic spline (RCS) analysis further reveals a “J-shaped” relationship between BRI and COPD, suggesting that BRI may serve as a potential predictive tool for COPD risk.